Leveraged Buyouts and Bankruptcy Risk - Remisha, Tassa (2013)
The issue of leveraged buyouts has always been associated with the increase of the likelihood of bankruptcy and the engagement of an intensive use of debt is deemed to be the primary cause. This study attempts to discern whether or not the LBO companies are subject to bankruptcy risk by applying the Cox proportional hazard model. The results of this study suggest that indeed the LBO companies are subject to a higher bankruptcy risk than other companies, yet leverage evidently is not the main cause of such bankruptcy. The study finds empirical evidence that the companies that are subject to an LBO underperformed their peers prior to the LBO suggesting that they have already had a higher risk of bankruptcy. The study also finds evidence that the risk of bankruptcy reduces post-LBO, affirming Jensen’s theory of privatization of bankruptcy.